Estudo ab initio das propriedades estruturais e eletrônicas de óxidos de tungstênio - Neto, Arquiminio Bomfim da Silva (Universidade Federal de São Carlos, 2022)
In the last two decades, tungsten oxide (WO3) has been a target of the scientific and technological interest community due to its optical and magnetic properties, which finds important applications such as sensors, electrochromic devices, protective layers against chemical attacks, photonics, hydrogen generation, among others. Owing to the need to understand and improve the properties of this class of material, it is essential to describe the electronic and structural behavior of these materials. By using one of the most successful protocols for solving the Schrödinger equation, the “Density Functional Theory”, this study focuses on the study of the structural and electronic properties of the cubic, hexagonal, tetragonal, orthorhombic, monoclinic and triclinic phases of tungsten oxide in order to provide fundamental insights into the understanding of the material.
Ab initio study of the structural and electronic properties of tungsten oxides
Keywords: WO3; Primeiros princípios; Band Gap; CASTEP; First principles; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::MATERIAIS NAO METALICOS